2018
DOI: 10.1097/wnf.0000000000000281
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Outcome of Adenosine A2A Receptor Antagonist on Lower Urinary Tract Symptoms in Male Parkinson Disease Patients

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…However, a recent study concluded that in PD patients, consumption of 200 mg coffee a day for 6 months did not improve the motor symptoms. Still, other clinical studies using the A2A receptor antagonist, istradefylline, are encouraging given that istradefylline significantly improved motor manifestations of PD and reduced nighttime urinary frequency (Jankovic, 2008;Matsuura and Tomimoto, 2015;Kitta et al, 2018).…”
Section: Natural Products Green Tea and Coffee To Reduce The Risk Of mentioning
confidence: 99%
“…However, a recent study concluded that in PD patients, consumption of 200 mg coffee a day for 6 months did not improve the motor symptoms. Still, other clinical studies using the A2A receptor antagonist, istradefylline, are encouraging given that istradefylline significantly improved motor manifestations of PD and reduced nighttime urinary frequency (Jankovic, 2008;Matsuura and Tomimoto, 2015;Kitta et al, 2018).…”
Section: Natural Products Green Tea and Coffee To Reduce The Risk Of mentioning
confidence: 99%
“…The first was prospective before‐after, the second was prospective non‐blinded clinical trial and the third was randomized clinical trial. The prospective before‐after studies by Brusa, Kitta, and Gubbiotti were in the field of medications. Crescenze and Brandi in a single prospective before‐after study evaluated the effect of SNM and parasacral electrostimulation, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, a larger-sized, placebo-controlled randomized study will need to be undertaken in order to confirm these results. Furthermore, our group also recently reported that significant improvements were observed during a 1-year istradefylline treatment of LUTS in PD patients [ 60 ]. Moreover, istradefylline may not only improve motor symptoms, but also LUTS in PD patients.…”
Section: Rodentsmentioning
confidence: 98%